DEMENTIA TRAINING FOR CONNECTICUT FAMILY CAREGIVERS: ENHANCING EXPERIENCES AND QUALITY OF SUPPORT. (11th November 2018) - Kellett, K; Wyman, M; O'Brian, P; Robison, J
Abstract: Individuals with dementia living in the community are mostly cared for by unpaid/family caregivers. Caring for an individual with a progressive brain disease can be overwhelming, and family caregivers frequently report a lack of training/understanding about dementia and access to community resources. Results of an evaluation of 16 dementia trainings, funded through a Money Follows the Person Demonstration Rightsizing grant and implemented by a community-based agency, with a sample of 137 family caregivers, showed an effect on three caregiver domains: self-efficacy, burden, and positive aspects of caregiving. Paired t-test results for the 5-item Caregiver Self-Efficacy Symptom Management scale showed a statistically significant increase from pre to post training (p < 0.001). For the 4-item Zarit Burden Interview, paired t-test results showed a statistically significant decrease in the mean burden level after the training (p = 0.005), and for the 4-item Carers of Older People in Europe (COPE) Index - Positive Aspects of Caregiving subscale, paired t-test results showed a statistically significant increase in the mean score after the training (p < 0.001). Outcomes suggest that caregiver dementia training improves caregiver confidence, the ability to manage daily care challenges, supports caregivers in their role and in the relationship they have with the care recipient, and should therefore continue to be consistently offered. Recommendations include additional research to evaluate the effectiveness of dementia training in community settings and further develop programs that provide practitioners with better ways to reduce the negative impacts of caregiving and enhance caregivers' experience and quality of support.